Comparison of metaraminol, phenylephrine and ephedrine in prophylaxis and treatment of hypotension in cesarean section under spinal anesthesia - Aragão,Fábio Farias de (2014)
Maternal hypotension is a common complication after spinal anesthesia for cesarean section, with deleterious effects on the fetus and mother. Among the strategies aimed at minimizing the effects of hypotension, vasopressor administration is the most efficient. The aim of this study was to compare the efficacy of phenylephrine, metaraminol, and ephedrine in the prevention and treatment of hypotension after spinal anesthesia for cesarean section. Ninety pregnant women, not in labor, undergoing cesarean section were randomized into three groups to receive a bolus followed by continuous infusion of vasopressor as follows: phenylephrine group (50 μg + 50 μg/min); metaraminol group (0.25 mg + 0.25 mg/min); ephedrine group (4 mg + 4 mg/min). Infusion dose was doubled when systolic blood pressure decreased to 80% of baseline and a bolus was given when systolic blood pressure decreased below 80%. The infusion dose was divided in half when systolic blood pressure increased to 120% and was stopped when it became higher. The incidence of hypotension, nausea and vomiting, reactive hypertension, bradycardia, tachycardia, Apgar scores, and arterial cord blood gases were assessed at the 1st and 5th minutes.There was no difference in the incidence of hypotension, bradycardia, reactive hypertension, infusion discontinuation, atropine administration or Apgar scores. Rescue boluses were higher only in the ephedrine group compared to metaraminol group. The incidence of nausea and vomiting and fetal acidosis were greater in the ephedrine group. The three drugs were effective in preventing hypotension; however, fetal effects were more frequent in the ephedrine group, although transient.